1992
DOI: 10.1002/1097-0142(19920401)69:7<1729::aid-cncr2820690714>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservationversus mastectomy. Is there a difference in psychological adjustment or quality of life in the year after surgery?

Abstract: Women with a breast cancer diagnosis often are given a choice between breast conservation or mastectomy as the primary treatment for their cancer. Despite the high frequency of this cancer, there is little systemic information about the effect of surgical treatment on the quality of life or psychological adjustment of the patient. In this study, the authors prospectively evaluated quality of life, performance status, and psychological adjustment in 109 women who had primary breast cancer treatment. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
148
3
14

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(174 citation statements)
references
References 34 publications
9
148
3
14
Order By: Relevance
“…In addition to global QOL, assessment of emotional functioning shows low levels at baseline too, with no significant changes during follow-up in both groups. An explanation for low levels at baseline is that patients being informed about the breast cancer diagnosis before surgery induced psychological distress (Fallowfield et al, 1986;Ganz et al, 1992;Coscarelli Schag et al, 1993). In this study the Karnofsky performance status score was, for most patients, over 90 at baseline and showed no differences in patients' physical condition in both groups during follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to global QOL, assessment of emotional functioning shows low levels at baseline too, with no significant changes during follow-up in both groups. An explanation for low levels at baseline is that patients being informed about the breast cancer diagnosis before surgery induced psychological distress (Fallowfield et al, 1986;Ganz et al, 1992;Coscarelli Schag et al, 1993). In this study the Karnofsky performance status score was, for most patients, over 90 at baseline and showed no differences in patients' physical condition in both groups during follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, Vinokur et al (1990) identified age in women with breast cancer (Lauria, 1991). Improved emotional responses and fewer rehabilitation problems were found in older rather than in younger cancer patients (Vinokur et al, 1990;Ganz et al, 1992;Moor et al, 1994).…”
mentioning
confidence: 87%
“…Other investigators reported no significant relationship between age and functional status (Vinokur et al, 1990;Ganz et al, 1992;Given et al, 1994). Current trends in health care aim to reduce hospital beds in acute care units.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the surgery in which the whole breast is removed) (e.g. Ganz et al, 1992a;Janz et al, 2005;Moyer, 1997;Poulsen et al, 1997). The only difference between surgeries appears to be on body image and sexual functioning, as patients treated with mastectomy report more concerns with appearance and more sexual difficulties than those treated with BCS (e.g.…”
Section: Introductionmentioning
confidence: 99%